Biopolymer-based formulations : biomedical and food applications - Pal, Kunal (Elsevier, 2020)
Presents the latest advances in the synthesis and characterization of advanced biopolymeric formulations and their state-of-the-art applications across biomedicine and food science. Sections cover the fundamentals, applications, future trends, environmental, ethical and medical considerations, and biopolymeric architectures that are organized in nano, micro and macro scales. The final section of the book focuses on novel applications and recent developments. This book is an essential resource for researchers, scientists and advanced students in biopolymer science, polymer science, polymer chemistry, polymer composites, plastics engineering, biomaterials, materials science, biomedical engineering, and more. It will also be of interest to R&D professionals, scientists and engineers across the plastics, food, biomedical and pharmaceutical industries. Key Features: Provides in-depth coverage of methods for the characterization of the physical properties of biopolymeric architectures. Supports a range of novel applications, including scaffolds, implant coatings, drug delivery, and nutraceutical encapsulation systems. Includes the use of experimental data and mathematical modeling, thus enabling the reader to analyze and compare the properties of different polymeric gels.--Provided by publisher.